Enhancement of interleukin-2 production by bovine peripheral blood mononuclear cells treated with the combination of anti-programmed death-ligand 1 and cytotoxic T lymphocyte antigen 4 chimeric monoclonal antibodies - WATARI, Kei; KONNAI, Satoru; OKAGAWA, Tomohiro; MAEKAWA, Naoya; SAJIKI, Yamato; KATO, Yukinari; SUZUKI, Yasuhiko; MURATA, Shiro; OHASHI, Kazuhiko (Journal of Veterinary Medical Science, 2022)
Our previous studies demonstrate the therapeutic efficacy against bovine diseases of an anti-bovine programmed death-ligand 1 (PD-L1) chimeric antibody. In humans, PD-1 and PD-L1 antibodies are more effective when combined with an antibody targeting cytotoxic T lymphocyte antigen 4 (CTLA-4) and these combination therapies are therefore clinically used. Here we generated an anti-bovine CTLA-4 chimeric antibody (chAb) to enhance the therapeutic efficacy of the PD-L1 antibody. We further analyzed the effects of dual blockade of CTLA-4 and PD-1 pathways on T-cell responses. The established anti-bovine CTLA-4 chAb showed comparable blocking activity on the binding of bovine CTLA-4 to CD80 and CD86 as the anti-bovine CTLA-4 mouse monoclonal antibody. Anti-bovine CTLA-4 chAb also significantly increased IL-2 production from bovine peripheral blood mononuclear cells (PBMCs). Further, the combination of anti-CTLA-4 chAb with anti-PD-L1 chAb significantly upregulated IL-2 production by PBMCs. These results suggest that the combination of antibodies have higher potential to enhance immune responses against pathogens compared with single administration.